A Capability Approach to Examining the Effects of Actual and Anticipated Fear of Crime: Experiences and Perceptions of Black Female Youth in the Cape Flats - Beiser, Sarina (Department of Social Development, 2021)
The purpose of this study was to examine how the fear of crime affects the capabilities, perceptions and experiences of black female youth, living in the Cape Flats, Cape Town. Qualitative semi structured interviews were conducted with 18 black female participants between the ages of 18 to 30. This study used Garofalo's model of fear of crime and Amartya Sen's capability approach as theoretical frameworks. With the help of these two frameworks, the researcher sought to gauge what influence the fear of crime can have on people's lives and how crime affects young black females living in communities with high crime rates. It also showed how their life choices and opportunities are influenced by living in unsafe communities. The major challenges and problems highlighted by the participants include: Constant trauma of their daily life (leaving their houses, random shootings, unsafe public transport), mental health issues (losing friends and relatives), lack of proper police service (lack of police presence, incompetence of police, corruption), fear for family or friends, lack of trust and support systems (broken families, loss of trust, no role models, lack of social capital), lack of infrastructure (such as safe hospitals or educational challenges), the effects of gangsterism (gangs and drug wars, effects of drugs, families' or friend's involvement in gangsterism) and the lack of opportunities such as unemployment. This study showed how the peoples' capabilities have been affected by the above-mentioned issues and how the fear of crime affected their daily lives. This study also made recommendations for policy makers and social institutions on what can be done to reduce crime rates and make communities with high crime rates safer